Safety and efficacy of interleukin inhibitors in elderly patients with rheumatoid arthritis, psoriasis, and psoriatic arthritis - Djuretić, Jasmina; Bufan, Biljana (Archives of Pharmacy, 2021)
Elderly patients with rheumatoid arthritis, psoriasis and psoriatic arthritis encompass those with elderly-onset disease, over 60 years of age, but also those with earlier disease onset who entered old age. Considering the age-related changes of the immune system, possible frailty, susceptibility to infection and concomitant comorbidity that implies multiple medicines, the treatment of these diseases in elderly patients can be challenging. Interleukin inhibitors have been shown to be an efficient and safe treatment for these diseases. However, elderly patients with these diseases were often included in the pivotal clinical trials for interleukin inhibitors in numbers insufficient to determine whether they responded differently from younger subjects. The aim of this paper was to review the findings on the efficacy and safety of interleukin inhibitor treatment in elderly patients with rheumatoid arthritis, psoriasis, and psoriatic arthritis. The findings suggest that, for all the interleukin inhibitors reviewed herein, used in elderly patients with rheumatoid arthritis, or with psoriasis and psoriatic arthritis, the efficacy was comparable to younger patients. Furthermore, the incidence of reported adverse events was similar in these two age groups. Severe adverse events, which were related to sarilumab treatment for rheumatoid arthritis and secukinumab treatment for psoriasis, were higher in elderly patients. The reviewed findings suggest that the interleukin inhibitors approved and currently in use in clinical practice for the treatment of rheumatoid arthritis, psoriasis, and psoriatic arthritis can be considered a safe and efficient option for these diseases in elderly patients.
Keywords: interleukin inhibitors; elderly patients; safety; efficacy